2016
DOI: 10.1002/adsc.201600155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐Aryl‐Substituted Indole‐3‐acetic Acid Derivatives via Intramolecular Imino‐Stetter Reaction of Aldimines with Cyanide

Abstract: Ag eneral method to generate umpolung of aldimines with cyanide was developed via the addition of cyanide to aldiminesf ollowed by ap roton transfer from the carbon atom to the nitrogen atom in the resulting cyanide adducts.T hisn ovel method was successfully applied to the first imino-Stetter reaction of aldimines obtainedf rom 2-aminocinnamic acid derivatives anda romatic aldehydes with cyanide,a ffording 2-aryl-substituted indole-3-acetic acid derivatives.F urthermore,t he usefulness of this method wass ucc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Specifically, NHC‐catalyzed cyclization of aldimines bearing a Michael acceptor afforded biologically important 2‐aryl indole 3‐acetic acid derivatives in moderate to good yields. Notably, the cyanide‐catalyzed umpolung of imines has recently been reported by Cheon and co‐workers . It is noteworthy that 2‐arylindole 3‐acetic acid derivatives are endowed with interesting biological properties and they are subunits in several natural products…”
Section: Methodsmentioning
confidence: 97%
“…Specifically, NHC‐catalyzed cyclization of aldimines bearing a Michael acceptor afforded biologically important 2‐aryl indole 3‐acetic acid derivatives in moderate to good yields. Notably, the cyanide‐catalyzed umpolung of imines has recently been reported by Cheon and co‐workers . It is noteworthy that 2‐arylindole 3‐acetic acid derivatives are endowed with interesting biological properties and they are subunits in several natural products…”
Section: Methodsmentioning
confidence: 97%
“…Under these conditions, various 2‐aminocinnamic acid derivatives 26 and aromatic aldehydes 2 could be applied to this protocol and the desired 2‐aryl substituted indole‐3‐acetic acid derivatives 24 were obtained in high to excellent yields (Scheme ) …”
Section: Synthesis Of 2‐substituted Indole‐3‐acetic Acid Derivatives mentioning
confidence: 99%
“…[ 19–21 ] Interestingly, catalysis using this concept has been extended to the umpolung reaction of Michael acceptors [ 22–25 ] and aldimines. [ 26–33 ] Detailed theoretical studies reported by our group [ 34–43 ] and other groups [ 44–52 ] have provided molecular‐level insight into the catalytic mechanism and chemo‐, regio‐, and/or stereo‐selectivities. [ 53,54 ]…”
Section: Introductionmentioning
confidence: 99%